Taking Measure of the UN's Legacy at Seventy-Five. Issue 3 (2020) - Malone, David M.; Day, Adam
Abstract: Over the past seventy-five years, the UN has evolved significantly, often in response to geopolitical dynamics and new waves of thinking. In some respects, the UN has registered remarkable achievements, stimulating a wide range of multilateral treaties, promoting significant growth of human rights, and at times playing a central role in containing and preventing large-scale armed conflict. As part of the special issue on "The United Nations at Seventy-Five: Looking Back to Look Forward, " this essay argues that the organization has been the most impactful in three areas: producing, shaping, and driving key ideas, particularly on development and rights; generating such effective operational agencies as UNICEF and the World Food Program; and, especially in the immediate post–Cold War period, addressing major conflict risks through the Security Council. Since then, however, the UN has struggled to meet emerging challenges on many fronts and been increasingly hampered by internal ossification and institutional sprawl as well as internecine dysfunction. The twenty-first century has confronted the UN with further challenges relating most notably to climate change; to risks arising from new technologies; and to the increasingly fraught relationships between China, Russia, and the United States. If the past seventy-five years can offer one lesson, it is that new thinking and new ideas will need to drive the organization to evolve still further and faster, or else risk irrelevance.